2D-Extension of Deployable Linked Panel Unit. Issue 4 (December 2014) - Takatsuka, Masao
The objective of the present paper is to propose a two-dimensional extension method for our previously proposed deployable 'linked panel unit' for construction of huge flat space-structures such as a solar power satellite. In our previous study, we proposed a one-directional extension method of the 'linked panel unit'. However, its two-dimensional deployment was assumed to be feasible with an additional mast. To address that issue, the present paper proposes a new 2D-extension method of the 'linked pane unit' without using an additional mast, and suggests it for realization of a solar power satellite as a huge flat construction in space.